Analysis of malaria control program implementation at the Riau Provincial Health Office - Vitriani, Viras; Hartono, Budi; Anusirwan, Anusirwan (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2026)
Background: The emergence of malaria outbreaks (Extraordinary Events/KLB) in certified elimination areas in Riau Province highlights persistent programmatic challenges. This study aims to assess the implementation of the malaria control program at the Riau Provincial Health Office, identify key barriers, and propose recommendations to enhance program effectiveness. Method: This study used a qualitative descriptive design with data collection through in-depth interviews, field observations, and analysis of related documents. Data analysis was carried out using a problem-solving cycle approach and Fishbone diagrams to identify the root causes of the problem. Results: Showed that the main obstacles in program implementation included low public awareness, limited budget, suboptimal policy implementation, and inadequate cross-sector coordination. The recommendations produced include increasing cross-sector collaboration, technical training for program holders, forming budget policy, intensive education and active community involvement, also strengthening sanitation infrastructure. Conclusion: The malaria control program in Riau Province requires a sustainable strengthening strategy to maintain malaria elimination status, especially with a community-based approach and increased multi-sector coordination.